Analysis of the Braking System in the Gardapati Prototype Energy Saving Car - Halim Davista; Syafri Syafri; Fablil Huda; Kaspul Anuar (Proksima, 2023)
The braking system is one of the crucial components in a vehicle because braking is a vital safety feature of the vehicle. The braking system functions to reduce or slow down the speed and stop the vehicle, as well as to enable the possibility of parking the vehicle on a downward slope. The braking system under investigation is examined in the prototype vehicle called Gardapati, which employs a hydraulic brake system. Gardapati is a vehicle created by students from the University of Riau's Mechanical Engineering Department, affiliated with the UKM Selembayung, following the standard references provided by the Energy-Efficient Vehicle Competition organized by BPTI. This final project will involve several calculations related to the braking system, following the specifications used in the Gardapati vehicle. First, calculations will determine the dynamic braking force required (Fb) when the vehicle is moving at a speed of 50 km/h with a distance of 20 meters, as well as the static braking force (Fb) required when the vehicle is on an incline of 11.2 degrees, adjusted to the requirements and regulations of the 2023 Energy-Efficient Vehicle Competition (KMHE). Then, the braking distance will be calculated for speeds of 30, 40, and 50 km/h on dry and wet asphalt road conditions. From the calculation results and data analysis, it is found that the required dynamic braking force (Fb) is 510,76 N, and the static braking force (Fb) is 830,31 N. Meanwhile, the minimum braking distance is observed on dry asphalt road conditions at a speed of 30 km/h with a percentage error of 1,59 %, where the theoretical value is 5.67 m and the actual value is 5,76 m. On the other hand, the highest braking distance is observed on wet asphalt road conditions at a speed of 50 km/h with a percentage error of 7,39%, where the theoretical value is 14.47 m and the actual value is 15.54 m. Of the two road conditions, the largest percentage error occurs when testing the vehicle at speeds of 30, 40, and 50 km/h on wet asphalt conditions, amounting to 4,61%. With this level of percentage error, it can be concluded that the variation in the obtained data is relatively small, which is less than 10%.